2017
DOI: 10.1007/s11367-017-1375-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the environmental impact of the conventional nickel electroplating and the new nickel electroplating

Abstract: Purpose To comply with the effluent regulation of boron, replacement of boric acid with citric acid in a nickel electroplating bath is proposed. Although the bath avoids the discharge of boron, it increases the discharge of nickel owing to the chelating effect of citric acid, which disturbs the wastewater treatment. To balance this trade-off, the environmental impacts of a traditional nickel plating process (the Watts bath) and the citrate bath must be compared by life cycle assessment. Methods The life cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…To further verify the role of the magnetic field for the deep deposition within the substrate, nickel was used instead of lithium to simulate the electroplating process on CF. [ 47 ] Figure S1a in the Supporting Information shows the simple schematic diagram of electroplating, where the red line on the left of CF shows that only this area is in contact with the electrolyte, and the arrow indicates the direction of movement of ions into the CF. The cross‐sectional digital photo images for the CF after Ni deposition are shown in Figure S1b,c in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the role of the magnetic field for the deep deposition within the substrate, nickel was used instead of lithium to simulate the electroplating process on CF. [ 47 ] Figure S1a in the Supporting Information shows the simple schematic diagram of electroplating, where the red line on the left of CF shows that only this area is in contact with the electrolyte, and the arrow indicates the direction of movement of ions into the CF. The cross‐sectional digital photo images for the CF after Ni deposition are shown in Figure S1b,c in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of boron in the bath waste is nonetheless reported to be harmful for the environment. Since the enforcement of Water Pollution Control Act in Japan [59] the imposed national minimum effluent standards have greatly influenced the electroplat- ing industry. Thus, it became necessary to find more environmentally friendly solutions for the electrodeposition of nickel and its alloys.…”
Section: Electrolytic Bath Compositionmentioning
confidence: 99%
“…When it comes to the environmental impact exerted by the electroplating process from either of the two baths: the one containing boric or the other containing citric acid, findings are quite contradictory. Takuma et al [59] applied a life cycle assessment method to demarcate the extent of their influence in terms of human toxicity and ecotoxicity. Results indicated that the newly developed citrate plating bath exerts higher environmental impact compared to the traditional Watts electrolyte, this owing to the release of nickel chelated with citric acid whose harmful influence overshadows the benefit of reduced boron emissions achieved by substituting boric acid in the electroplating bath.…”
Section: Electrolytic Bath Compositionmentioning
confidence: 99%
“…Therefore, the environmental impact of these chemicals needs to be evaluated and reduced through suitable treatment of industrial wastewater. [ 1 ] Heavy metals, such as zinc, copper, and chromium, are harmful to the environment and human body [ 2,3 ] ; therefore, the concentrations of these metals in effluents are strictly regulated. [ 4 ] In Japan, the effluent standard value for zinc is 2 mg/L.…”
Section: Introductionmentioning
confidence: 99%